]]>
LearnNext
Get a free home demo of LearnNext

Available for CBSE, ICSE and State Board syllabus.
Call our LearnNext Expert on 1800 419 1234 (tollfree)
OR submit details below for a call back

clear

Sum of first n terms of an AP

6,607 Views
Have a doubt? Clear it now.
live_help Have a doubt, Ask our Expert Ask Now
format_list_bulleted Take this Lesson Test Start Test

Sum of first n terms of an AP - Lesson Summary

Deriving the Formula for Sum of n Terms

Consider a standard arithmetic sequence, where

a = first term

d = common difference, and

n = number of terms

S = sum of the terms

Consider the reverse of this AP. In the reversed AP, the last term, [a + (n-1)] d, appears in the first position, and the first term, a, in the last position. The sum of the terms of this AP also will be S.

Corresponding terms of of both the APs are added, that is, first term to first term, second term to second term and so on.

The sum of the corresponding terms is equal in every case.

The sum of the terms is [2a + (n-1)] d in every case.

= a + a +(n - 1)d

= 2a +(n - 1)d

= a + d + a +(n - 2)d

= 2a +(n - 1)d

= a + d + a +(n - 2)d


= 2a +(n - 1)d

= a + a +(n - 1)d

= 2a +(n - 1)d

⇒ 2S = n x [2a + (n - 1)d]

⇒ S = n/2 x [2a + (n - 1)d]

⇒ S = n/2 x [a + a + (n - 1)d]

⇒ S = n/2 [First term + Last term]

⇒ S = n/2 [a + l]

Comments(0)

Feel the LearnNext Experience on App

Download app, watch sample animated video lessons and get a free trial.

Desktop Download Now
Tablet
Mobile
Try LearnNext at home

Get a free home demo. Book an appointment now!

GET DEMO AT HOME